(3RgQ GdceGe aj bUI jhSa Ydjg GdSdGes - (3YeQ Hf EHQGgje Hf YeQ, SQGL GdOjf, CHh MaU GdCfUGQj GdChSj GdoerQSj,J (B751 (3g` s ((3YHO Gddg Hf bGSeI GdQhei GdHgTJi s)
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf cKjQG hUdi Gddg Ydi SjOfG eMeO GdPi CQSdg ddfGS cGaI HTjQkG s
(3BNQgG (B:s
(3aLfGHg QMH dcd eDed hgh GdEdg GdhGMO GdbgGQ s
(3PcQ HQhcdeGf (B2 :265 (3Cf GSe GdeDda gh CHh GSMGb GHQGgje Hf eMeO Hf jMji Hf CMeO Hf RcQjG GHf jMji GdCfUGQj GdBhSi GdeQSi SfI (B751s
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B39s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B3 - (3U (B7 s
Keywords: (3GdJGQjNs